Incidence, knowledge, attitude and practice toward needle stick injury among nursing students in Saudi Arabia - Al-Mugheed, Khalid; Farghaly, Sally Mohammed; Baghdadi, Nadiah A.; Oweidat, Islam; Alzoubi, Majdi M. (Frontiers in Public Health, 2023)
Background Needle stick injuries constitute the greatest threat to nursing students during clinical practice, mainly because of accidental exposure to body fluids and infected blood. The purpose of this study was: 1) to inspect the prevalence of needle stick injuries and 2) to measure the level of knowledge, attitude and practice among nursing students about needle stick injuries. Methods: A cross-sectional and descriptive study design was conducted among undergraduate nursing students in private college in Saudi Arabia. Three hundred participants were included, of whom only 281 accept to participate with a response rate of 82%. Results: The prevalence of at least one incident of needle stick injuries among our sample was 14.1% (n= 47). The participants showed good knowledge scores with a mean score of 6.4 (SD = 1.4), results showed that students have positive attitudes (M= 27.1, SD=4.12). Students reported a low level of needle stick practice (M = 14.1, SD = 2.0). The total prevalence of needle stick injuries among our sample was 14.1%. The majority of them 65.1% reported once incidence in last year, while (24.4%) 15 students reported NSI twice. The recapping was the most incidence occurred (74.1%), followed by during injection (22.3%). The majority of students did not write a report (77.4%), and worried and afraid were the main reasons for non-report (91.2%). The results showed that female students and seniors scored higher in all needle stick injuries domains than male students and juniors. Students who got needle stick injuries more than 3 times last year reported a lower level of all needle stick injuries domains than other groups (M = 1.5, SD =1.1; M = 19.5, SD =1.1; M = 9.5, SD =1.1 respectively). Conclusion Raising awareness among nursing students and conducting continuing education related to sharps devices and safety is highly recommended. The policymaker should implement several initiatives to reduce the needle stick injuries incidence such as safe injection practices, safety precautions, reporting systems, and use of post-exposure prophylaxis.